BUILDING A CHARACTER OF BUSINESS DOER THROUGH INTERNALIZATION OF VALUES ON PANCASILA AS A SOUECE OF BUSINESS ETHICS IN INDONESIA TO FACE ASEAN COMMUNITY 2015 - -, Siti Supeni (PROCEEDING INTERNASIONAL SEMINAR, 2015)
ASEAN Community is a community built in November 20th 2007 as a result of the development of the concept of ASEAN at the past. It was built as the organization focusing on politics and security community, economic community, and ASEAN culture social community. The main purpose of it is to create a vision and identity harmoniously. The problem that will be discussed in this paper is how to build a character of business doer through internalization of values on Pancasila as a source of business ethics in Indonesia. The results of discussion are (1) socializing values of pancasila as a source of ethics rule toward business doer from ASEAN country is a must although it need times and strategy; (2) the use of language ethics on business activities is based on the values of pancasila; (3) and spreading various ethics from other ASEAN nations toward Indonesia is a natural and ordinary phenomenon but selecting the most appropriate based on the ideology of pancasila is compulsory. In conclusion, keeping values on pancasila not only as the ideology of Indonesia but also as a source of ethics rule is crucial. Also spreading them to affect other ASEAN nations is needed to build nations of ASEAN that has the ideology of pancasila.Keywords: Values on Pancasila, Business Ethics and ASEAN community.